The Role of Financial Instruments and their Impact on the SME Sector - Dumitru NANCU (Revista de Management Comparat International, 2017)
This paper deals with the role of the financial instruments and with their impact on the SME sector, in connection to the Cohesion Policy 2014-2020 and the objectives of Europe 2020 Strategy. For this purpose, the first part of the work presents several general considerations on the financial instruments, while the second part analyzes the main types of financial instruments, with a focus on their importance and role in the SME sector.